Marketing relacional y fidelización de clientes en el Centro Odontológico Denti Laser, Trujillo, año 2018 - Gil Cruzado, Patricia Katherine (2019)
This thesis was held in the city of Trujillo, Province of Trujillo, La Libertad Region, with the Denti Laser Dentistry Center as the object of study. Its general objective was to establish the relationship that exists between relational marketing and customer loyalty in the company under study; In this regard, the problem was: What is the relationship between Relationship Marketing and Customer Loyalty at Denti Laser Dentistry Center, Trujillo, year 2018? The study population was represented by 310 active clients, with the respective sample being 111 clients to whom the survey technique was applied, whose instrument was the questionnaire; the research design used was non-experimental, descriptive type transectional or cross-correlational. After the respective analysis of the results has confirmed the hypothesis that establishes that there is a positive relationship between relational marketing and customer loyalty in Denti Laser Dental Center, Trujillo, year 2018; the main conclusion is that the relationship between relationship marketing and customer loyalty is positive, considering that the Pearson Correlation Coefficient is 0.682, which means that if the independent variable is presented as a strength, the dependent variable will also do so, also demonstrating a direct relationship. It is recommended that Denti Laser look for alternatives to create lasting relationships with its clients, in order to achieve loyalty, and whenever they need it, they acquire the services favoring the profitability of the company.